Governança para a administração pública federal: avaliação das práticas das universidades federais da Região Sul - Minuzzi, Danielle (2022)
A scenario of constant transformations demands from public managers new ways of managing the public sector, it’s up for public managers understanding society's needs and implementing managerial concepts capable of carrying out their policies and government programs in response to society's, aiming for an agile, transparent and consistent public management with the volume of resources that are competent. In this way, governance offers mechanisms and instruments capable of supporting public organizations towards a more efficient management focused on the public interest. Inserted in this context, and object of this study, are the federal universities. This paper aims to identify the best governance practices for federal universities in southern Brazil based on the governance principles and practices proposed by the International Federation of Accountants (IFAC) and the Chartered Institute of Public Finance and Accountancy (CIPFA) . With a study universe encompassing the eleven federal universities in southern Brazil, this work falls within the field of applied research and, according to its objectives, is classified as descriptive. Thus, a verification of three of the four dimensions of governance proposed by Study 13 (IFAC, 2011) was carried out on university websites, and a questionnaire was applied to the members of university councils to verify a fourth dimension. To collect data from the International Framework: Good Governance in the Public Sector (IFAC; CIPFA, 2014), a questionnaire was applied to the members of university councils. Among the main results, a medium level of adherence to the Study 13 model was identified, and a high level of adherence to the International Framework of good governance in the public sector. It was detected that the greatest strengths refer to the annual management and accounting reports, issued annually in accordance with a series of regulations that guarantee a standard in the presentation of these documents, which are important instruments of transparency and accountability of federal universities. Another positive point refers to the list of documentation implemented or developed, to a greater or lesser degree, by the institutions themselves, as well as the creation of bodies/sectors/commissions responsible for matters related to governance. Regarding the most deficient points, it was found that no university has an Audit Committee, a body that could act as an auxiliary instance and/or additional line of control, in view of the massive list of attributions covered by the Internal Audit bodies, which may run the risk of acting as the only instance of internal control in these institutions. Nor were found documents establishing the financial strategy. It was noted that the universities with the highest scores in one framework had the worst results in the other, which may represent a gap between the perception of the board of directors and the governance practices undertaken by the institutions. The results obtained indicate an evolution, since the research by Sales (2014), in the adoption of governance practices by universities, which suggests that the development is due to the intensification of regulations issued by the control bodies. This panorama provides support for proposing a model of good governance practices in federal universities.